The Development of Horner Syndrome following a Stabbing - Muhammet Sayan; Ali Çelik (Case Reports in Medicine)
The features of Horner Syndrome are miosis, ptosis, enophthalmos, and anhidrosis on the same side as the etiologic pathology. Its causes include tumours, aneurysms, neck and chest surgery, and neck and chest trauma. This paper presents a case of Horner Syndrome due to a haemopneumothorax following penetrating chest trauma.